Comprehensive Surgical Strategies for the Management of Pachydermoperiostosis - Taichao, Du; Fuling, Luo; Hengguang, Zhao (Facial Plastic Surgery, 2018)
The cosmetic and functional deformities induced by thickened folds and furrows are the main complaints of patients in pachydermoperiostosis (PDP). However, traditional drug therapy only has a limited effect for its unclear genetic pathogenesis. Surgical treatment has now become one of the optimal strategies mainly aiming for its cosmetic improvement. Here we describe a comprehensive management of PDP approached with surgical procedure thereby showing markedly improved cosmetic outcome. Experientially, the surgical treatment of PDP is effective and may be preferentially recommended for PDP patients especially of severe degree.
Keywords: pachydermoperiostosis; surgery; rhytidectomy; expander; autologous tissue padding